(untitled) (Research, Society and Development, 2021)
Objective: To investigate the main pain complaints indicative of Work-Related Musculoskeletal Disorder (WMSD) among nursing professionals. Methodology: This is an integrative literature review, with a search in the following databases: Latin American and Caribbean Health Science Literature (LILACS), Scientific Electronic Library Online (SciELO), Medical Literature Analysis and Retrieval System Online (MEDLINE), National Library of Medice (PubMed) and Google Academic. Articles published in the last 5 years (2016 - 2021), in Portuguese and English, that presented in their direct content with the proposed theme were used. Results and discussion: 11 articles were selected. The main complaints and symptoms indicative of WMSD mainly involve pain in the lumbar region, neck, upper and lower limbs, with low back pain or the main symptom self-reported by nursing professionals. The main etiological factors of WMSD are related to postures exercised during work, long working hours and high rates of mechanical exposure, in addition to the lifting and handling of materials that result in high loads in the most reported regions of the body. Conclusion: There is a high rate of work-related pain in nursing professionals. The main complaints are pain conditions with prevalence in the lumbar region, associated with the organization of work and the biomechanics exercised during work activities. It is suggested to carry out more in-depth studies on the subject, which can support increasingly assertive interventions in terms of quality of life at work and health promotion for professionals.